Relationship between patient safety culture and professional conduct of nurses in context of clinical governance implementation - Farshad Jabari; Maryam Ooshaksaraie; MohammadReza Azadehdel; Fardin Mehrabian (Guilan University of Medical Sciences, 2015)
Abstract Introduction: Providing proper and qualified nursing care for patients as members of society has turned patient safety to an important issue in quality health care in country. . Objective: This study aims to determine the relationship between patient safety culture and professional behavior of nurses within the framework of the implementation of clinical governance in all health centers in Rasht. Methods: This study is a descriptive and correlational study whose statistical population consisted of nurses in health centers in Rasht city, of which 322 patients were selected randomly as samples. Data collection tool included nurses professional behavior taken from Wakefield instrument and Research Agency questionnaire and quality of health care for patient safety culture. Data were analyzed using descriptive statistics and Pearson correlation coefficient. Results: Findings indicated from respondents' views, nurses professional behavior and patient safety culture in educational health centers in Rasht was at moderate level. The results also showed a significant and direct relation between professional behavior of nurses and patient safety culture (P <0.01, r=0.6). Conclusion: Patient safety culture will improve as nurses professional behavior increases. It seems to an enabling program can create an atmosphere in which people feel more responsible conducting professional behavior and increase culture of patient safety.